Persistence of patient and family experiences of critical illness - Ramona O Hopkins; Eliotte L Hirshberg; Jorie Butler; Morgan Francis; Francis A Davis; Doriena Lee; Fahina Tavake-Pasi; Edwin Napia; Jeanette Villalta; Valentine Mukundente; Heather Coulter; Louisa Stark; et al. (BMJ Open)
Objective To investigate: (1) patient and family experiences with healthcare and the intensive care unit (ICU); (2) experiences during their critical illness; (3) communication and decision making during critical illness; (4) feelings about the ICU experience; (5) impact of the critical illness on their lives; and (6) concerns about their future after the ICU.Design Four semistructured focus group interviews with former ICU patients and family members.Settings Multicultural community group and local hospitals containing medical/surgical ICUs.Participants Patients and family who experienced a critical illness within the previous 10 years.Interventions None.Measurements and main results Four separate focus groups each lasting a maximum of 150 min and consisting of a total of 21 participants were held. Focus groups were conducted using a semistructured script including six topics relating to the experience of critical illness that facilitated deduction and the sorting of data by thematic analysis into five predominant themes. The five main themes that emerged from the data were: (1) personalised stories of the critical illness; (2) communication and shared decision making, (3) adjustment to life after critical illness, (4) trust towards clinical team and relevance of cultural beliefs and (5) end-of-life decision making. Across themes, we observed a misalignment between the medical system and patient and family values and priorities.Conclusions The experience of critical illness of a diverse group of patients and families can remain vivid for years after ICU discharge. The identified themes reflect the strength of memory of such pivotal experiences and the importance of a narrative around those experiences. Clinicians need to be aware of the lasting effects of critical illness has on patients and families.